Critical Study of the Implementation of the Right of Self-Determination in Protecting Indonesia’s Environmental and Economic Sovereignty - Sudarmo Sudarmo; Febrianty Yenny; Putri Viorizza Suciani; Muhtar Mohamad Hidayat; Salahuddin Salahuddin (E3S Web of Conferences)
Indonesia’s claim to self-determination is challenged by the nation’s dependence on foreign economic interests, particularly in the management of its natural resources. As foreign nations and corporations enter through investment and employment contracts, they often gain equal footing with domestic entities, which undermines Indonesia’s control over its environmental resources. The lack of autonomous management of these resources, coupled with policies favoring foreign interests, raises concerns about Indonesia’s environmental sovereignty. This research aims to examine how the Right to Economic Self-Determination Principle can be leveraged to protect Indonesia’s environmental and economic sovereignty. Given its philosophical and analytical orientation, along with its descriptive and normative legal analysis, this study falls under the category of normative legal research. The findings indicate that Indonesia’s reliance on foreign investment and inadequate regulations, such as inequitable contracts related to environmental resource exploitation, challenge the nation’s commitment to self-determination. Additionally, the burden of foreign debt further hinders the effective exercise of this right. There is a pressing need to reharmonize the spirit of environmental and economic freedom, as enshrined in the 1945 Constitution, with current laws. This includes restructuring contracts and agreements with foreign entities involved in Indonesia’s environmental sectors to ensure alignment with national sovereignty.